The law of nuclear energy - Cook, Helen (United Kingdom: Thomson Reuters, 2022)
This brand new text by legal experts Helen Cook is a handbook for nuclear law, covering all aspects of the legislative framework for nuclear power and nuclear power projects. Required reading for anyone operating, practicing or studying in this field.
Part I. Legal infrastructure for nuclear energy -- 1. Nuclear energy for policy makers -- 2. Introduction to nuclear energy law -- 3. Developing a nuclear power programme -- 4. International nuclear law -- 5. National nuclear law -- 6. Nuclear regulation -- 7. Nuclear Liability -- Part II. Nuclear power new build -- 8. Introduction to nuclear power new build -- 9. Procurement -- 10. Construction -- 11. Financing nuclear power projects -- 12. The nuclear fuel cycle- front end -- 13. The nuclear fuel cycle- back end -- Part III. Future of nuclear law -- 14. Small modular nuclear reactors -- 15. Future developments in nuclear energy law -- Appendices.
Puan Shaizimah Badzri (Bacaan Asas FUU)/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 0389216390/ OC/ Bookline Services
Includes index.
Keywords: Nuclear energy -- Law and legislation